IMPLEMENTASI PERATURAN DAERAH PROVINSI RIAU NOMOR 1 TAHUN 2015 TENTANG RETRIBUSI PERPANJANGAN IZIN MEMPEKERJAKAN TENAGA KERJA ASING - Putri, Lisa Eka; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Local governments set policies to regulate and control the used of foreign workers that working in Riau province and make the retribution of extension of employment license of foreign worker to become the local revenue through Riau Province Regional Regulation No. 1 of 2015 About Retribution of Extension of Employment License of Foreign Workers. Along with the implementation of this Regional Regulation, related problems that are still found in foreign workers are their work permit period has been exhausted but still can work in Riau province. Other than that, the application of all aspects that exist in the Regional Regulation still can not be applied maximallyThe purpose of this study is to find out how the application and the factors that influence the implementation of Riau Province Regional Regulation No. 1 of 2015 About Retribution of Extension of Employment License of Foreign Workers. This research uses the concept of policy implementation theory according to Riplay and Franklin in Tahir (2015: 95) about the success of policy implementation based on three perspectives, that are: level of bureaucratic compliance, smooth routines, no problems and performance. This research uses qualitative method with descriptive data assessment. In collecting data, researchers used interview techniques, observation, literature study and documentation by using purposive sampling method as source of information and data analysis. Results of research related to the implementation of Riau Province Regional Regulation No. 1 of 2015 Retribution of Extension of Employment License of Foreign Workers that known not yet running maximally, which is caused by influencing factors, namely the distribution of authority of the implementor is less tailored to the division of tasks, socialization that has not been maximized and the lack of human resources of employment controller, so that the implementation of retribution of extension of employment license of foreign workersi is not running maximallyKeywords: Policy Implementation, Retributions of Permissions, Foreign Workers